1/3(12x-24)=16
*3 *3
12x-24=48
+24 +24
12x=72
/12 /12
x=6
Answer:
7x2 + 4 x + 20
Step-by-step explanation:
Subtract 3x2 from 10x2.7x2+10x+20−6xSubtract 6x from 10x.7x2+4x+20
Step by Step Solution
More Icon
STEP
1
:
Equation at the end of step 1
(((2y - 1)2) - 4 • (2y - 1)) + 4
STEP
2
:
Trying to factor by splitting the middle term
2.1 Factoring 4y2-12y+9
The first term is, 4y2 its coefficient is 4 .
The middle term is, -12y its coefficient is -12 .
The last term, "the constant", is +9
Step-1 : Multiply the coefficient of the first term by the constant 4 • 9 = 36
Step-2 : Find two factors of 36 whose sum equals the coefficient of the middle term, which is -12 .
-36 + -1 = -37
-18 + -2 = -20
-12 + -3 = -15
-9 + -4 = -13
-6 + -6 = -12 That's it
The formula for compound interest
A = P( 1 + r/n) ^ (nt)
A is the amount in the account at the end
P is the principal balance or the amount initially invested
r is the annual interest rate in decimal form
n is the number of times it is coupounded per year
t is the number of years
A = 1800 ( 1+ .0375/1) ^ (1*6)
A = 1800 ( 1.0375)^6
A = 2244.92138
Rounding to the nearest cent
A = 2244.92
Answer:
4m
Step-by-step explanation: